The Role of Digital Accounting in Improving the Business of Micro, Small and Medium Enterprises (MSMEs) Warkop Agam - Ginting, Berupilihen Br (CV. Rayyan Dwi Bharata, 2025)
The company's objectives can be effectively carried out by utilizing an information system that has been automated in the company's business activity pattern. Digital transformation in business activities refers to the transformation of the company's financial management in the representation of accounting information systems with the use of digital formats. The use of collaboration in accounting systems and technology can provide business owners with the opportunity to increase efficiency and effectiveness in decision making. In this study, data collection techniques were carried out through literature studies of library materials and in-depth interview methods with micro, small and medium enterprises (MSMEs) of agam warkop in Medan City. The results of interviews and literature studies were analyzed so as to answer research questions, Digital accounting can help improve business performance, Computerized bookkeeping helps in recording inventory and sales records, which greatly helps computerized records, financial reporting with, using digitalization makes it easier for businesses to use financial reports as a decision-making tool.